PELAKSANAAN PROSES PENUNTUTAN PERKARA TINDAK PIDANA KORUPSI DI KEJAKSAAN TINGGI JAWA TENGAH - Galih Hartanto Putro, Sukinta, Bambang Dwi Baskoro (Diponegoro Law Journal, 2012)
Corruption   in   Indonesia   is   still   going   and   continues   to   increase. Development continues to increase from year to year, both in number of cases and the amount of financial loss  to the state and in terms of the quality of criminal offenses committed more systematic and  scope to enter all aspects of society. Corruption in Indonesia has also been extended to  various sectors. The human body is like a "cancer" malignant corruption continue to undermine vital nerves in the body so that the country of Indonesia institutional crisis. Cases of corruption are not just happening at the national level only, in the areas of corruption cases is almost the same as it did at the central level. There needs to be a serious treatment of the law enforcement officers  in his special anti-corruption that occurred in Central Java. From the background that has been submitted, it can be drawn a problem of how  coordination between the police, prosecutors, and the Commission in handling corruption cases, how the implementation of the prosecution case in the prosecution  of  corruption  high  central  java,  and  what  obstacles  are  occurred during the prosecution of corruption cases.  From research conducted aimed to determine the handling of corruption cases, and coordination among its agents, as well as any obstacles that occur during the examination process. From the research that has been done can be drawn a conclusion: (1) The partnership between the police, prosecutors, and the Commission can basically be divided into two terms, namely the functional and institutional relationships. (2) The prosecution of criminal cases is a very important part in the criminal justice system  as  a  "bridge"  that  connects  the  investigation  stage  to  the  stage  of examination in court. In addition, the objectives of the prosecution is a "filter" or filters to a case file is whether it deserves to be transferred to the  court. (3) Obstacles encountered in the prosecution of corruption cases were divided into 2 obstacles that are non judicial and juridical obstacles.